The Traitor Prince : A Ravenspire Novel - Redwine, C. J. (New York Balzer + Bray, an imprint of HarperCollinsPublishers, 2018)
Javan Najafai, crown prince of Akram, has spent the last ten years at an elite boarding school, far away from his kingdom. But his eagerly awaited return home is cut short when a mysterious impostor takes his place and no one believes Javan is the true prince
Keywords: Princes -- Impostors and imposture -- Slaves